IMPLEMENTATION OF AIR QUALITY DETECTION SYSTEM FOR HEALTHY ENVIRONMENTAL MONITORING - Kurnia Sirni, Dian Yudha; Nofriadi, Nofriadi; Sahren, Sahren (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: The increasing number of students at STMIK Royal Kisaran has raised the risk of air pollution caused by vehicle emissions, cigarette smoke, and waste burning, particularly around the campus canteen. The campus's location, which is close to a rubber factory and the Sumatra Crossroad, further exacerbates air quality and significantly impacts the health of individuals active at STMIK Royal. This study aims to develop a system that can measure air quality in real-time and detect pollutants in the campus environment. The system utilizes MQ-135 and MQ-2 sensors integrated with a microprocessor to process and transmit data to an IoT-based database. This research employs a qualitative descriptive method to describe the facts and trends based on the available data. The results indicate that air quality is good in the morning, worsens during the afternoon, and improves again in the evening, reflecting increased pollution during periods of heightened industrial and transportation activities. The implementation of this system is expected to contribute to the creation of a healthier environment and raise awareness about the importance of air quality.Keywords:  air quality; campus environment ; IoT; pollution. Abstrak: Peningkatan jumlah mahasiswa di Kampus STMIK Royal Kisaran telah meningkatkan risiko polusi udara akibat asap kendaraan, rokok, dan pembakaran sampah, terutama di sekitar kantin kampus. Lokasi kampus yang dekat dengan pabrik karet dan jalan lintas Sumatera sehingga memperburuk kualitas udara dan sangat mempengaruhi kesehatan para individu yang beraktivitas di STMIK Royal. Penelitian ini bertujuan mengembangkan sistem yang dapat mengukur kualitas udara secara real-time dan mendeteksi polutan di lingkungan kampus. Sistem ini menggunakan sensor MQ-135 dan MQ-2 yang terintegrasi dengan mikroprosesor untuk mengolah dan mengirim data ke database berbasis IoT. Penelitian ini menggunakan metode deskriptif kualitatif untuk menggambarkan fakta dan kecenderungan dari data yang tersedia. Hasilnya menunjukkan bahwa kualitas udara baik di pagi hari, memburuk di siang hari, dan membaik lagi di sore hari, menunjukkan peningkatan polusi saat aktivitas pabrik dan transportasi meningkat. Implementasi sistem ini diharapkan dapat mendukung terciptanya lingkungan yang lebih sehat dan meningkatkan kesadaran akan pentingnya kualitas udara.Kata kunci: IoT; lingkungan kampus; kualitas udara; polusi.